Increasing the Knowledge of TPQ Al-Amanah Mandiri Children About the Importance of Having Area Since Early in RT 04 RW 13 Cijujung Village, Bogor District - Widianto, Sinta; Umam, Amalul (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
Real Work Lecture (KKN) is a student activity in serving the community with an cross-scientific and sectoral approach at a certain time and area. The Indonesian Directorate General of Higher Education requires every tertiary institution to carry out KKN as an intracurricular activity that combines the tri dharma of higher education, namely: education, research, and community service. The implementation of the Ibn Khaldun University Offline KKN activities took place from September 6 to September 26 2021 and took place at RT 04 RW 13, Cjujung Village, Sukaraja District, Bogor Regency. In implementing the Offline KKN students conducted a seminar entitled The Importance of Having Aspirations at TPQ Al-Amanah Mandiri, Cijujung village. This seminar aims to increase children's insight and motivation from an early age so that they have and plan for future goals. The participants who attended this seminar totaled 20 children aged 6-13 years who were elementary school and junior high school students. The final result obtained in this seminar is that all participants have very diverse aspirations including Police, Ustadz, Teachers, Soldiers, Youtubers, Doctors, Athletes, Firefighters, and Chefs.